Confiscation of funds in Islamic law (Journal of the College of Basic Education, 2022)
The confiscation of funds in Islamic law is the appropriation of money that is condemned to be taken, destroyed, or expelled from his property by selling as a punishment, and this punishment is a deterrent and a rebuke for the perpetrators.